Integrated Epigenetics, Transcriptomics, and Metabolomics to Analyze the Mechanisms of Benzo[a]pyrene Neurotoxicity in the Hippocampus. (31st July 2018) - Wang, Jing; Li, Chun-Lin; Tu, Bai-Jie; Yang, Kai; Mo, Ting-Ting; Zhang, Rui-Yuan; Cheng, Shu-Qun; Chen, Cheng-Zhi; Jiang, Xue-Jun; Han, Ting-Li; Peng, Bin; Baker, Philip N; et al.
Abstract: Benzo[a]pyrene (B[a]P) is a common environmental pollutant that is neurotoxic to mammals, which can cause changes to hippocampal function and result in cognitive disorders. The mechanisms of B[a]P-induced impairments are complex .To date there have been no studies on the association of epigenetic, transcriptomic, and metabolomic changes with neurotoxicity after B[a]P exposure. In the present study, we investigated the global effect of B[a]P on DNA methylation patterns, noncoding RNAs (ncRNAs) expression, coding RNAs expression, and metabolites in the rat hippocampus. Male Sprague Dawley rats (SD rats) received daily gavage of B[a]P (2.0 mg/kg body weight [BW]) or corn oil for 7 weeks. Learning and memory ability was analyzed using the Morris water maze (MWM) test and change to cellular ultrastructure in the hippocampus was analyzed using electron microscope observation. Integrated analysis of epigenetics, transcriptomics, and metabolomics was conducted to investigate the effect of B[a]P exposure on the signaling and metabolic pathways. Our results suggest that B[a]P could lead to learning and memory deficits, likely as a result of epigenetic and transcriptomic changes that further affected the expression of CACNA1C, Tpo, etc. The changes in expression ultimately affecting LTP, tyrosine metabolism, and other important metabolic pathways.